PENGENDALIAN PENYAKIT LAYU Fusarium PADA BAWANG MERAH (Allium ascolonicum L.) DENGAN Gliocladium sp. dan Trichoderma sp. - Silvano, Jesis; Wirya, Gusti Ngurah Alit Susanta; Khalimi , Khamdan (Agriculture Faculty of Flores University, 2025)
One of Indonesia's most valuable commodities is scallions, a type of onion known as Allium ascalonicum L. Wilt disease, caused by Fusarium sp., poses significant challenges to shallot production. Curled, light-green leaves, along with complete plant death, are symptoms of this disease, which reduces harvest yields. To manage Fusarium wilt in shallots, this research aims to assess the efficacy of antagonistic fungi, namely Trichoderma sp. and Gliocladium sp. The research used in vitro testing to determine how well the fungus inhibited the growth of Fusarium sp., and in vivo studies to assess how well the control worked in the real world. The active chemicals that were generated were identified by Gas Chromatography-Mass Spectrometry (GC-MS) analysis. With an inhibitory power of 77%, Trichoderma sp. topped the list, followed by Gliocladium sp. with 75%.